Using process drama in EFL education: A systematic literature review - Luo, Shujie; Ismail, Lilliati; Ahmad, Norhakimah Khaiessa; Guo, Qian (Elsevier, 2024)
Process drama, which emphasizes the active exploration of fictional roles and situations, has proven to be an effective pedagogical approach in language teaching and learning. Despite its recognized efficacy, the systematic evaluation of process drama’s impact on English as a Foreign Language (EFL) education remains understudied. This systematic review aimed to investigate the current literature on the relationship between process drama and EFL teaching and learning. Using the keywords "process drama" and "EFL," publications released between 2003 and 2023 were meticulously extracted from various reputable databases, including ProQuest Citation, Web of Science, Scopus, Science Direct, Taylor & Francis, SAGE, and Google Scholar. In total, 30 studies (27 articles, two master’s theses, and one PhD thesis) that met the inclusion criteria were analyzed comprehensively based on their primary characteristics, fostering in-depth discussions on the diverse factors influencing EFL learning and teaching through process drama. Notably, the review underscores that process drama exerts a significant and positive impact on EFL learning and teaching, particularly by enhancing language skills, students’ language learning outcomes, and EFL teacher development.